Construcción artística dentro del contexto de la Cdla. La Libertad, del cantón Pasaje - Palacios Zambrano, Ángela Jacqueline (2015)
This proactive research project was developed in the citadel La Libertad located on the road to Cuenca against the citadel of Canton Pasaje Las Nieves . This is a community comprised of asset-liability soldiers and civilians , which are engaged in different activities of a social group. Within this context, it performs a printing workshop as a technique to link the people of this community in artistic practice .